ANALISIS FINANSIAL APLIKASI DOSIS DAN JENIS PUPUK ORGANIK CAIR TERHADAP PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill) - Tri Waluyo (Universitas Nasional, 2020)
Tomato (Lycopersicon esculentum Mill) is a type of fruit vegetable, very good to be developed because it has a high economic value, has a unique taste, which is a combination of sweet and sour flavors, making tomatoes one of the fruits that are in great demand by the public. Tomatoes can be consumed fresh or processed into juice and a mixture of cooking spices. Industry players use tomatoes for sauces, cosmetic ingredients, and even as ingredients for medicines because they contain protein, carbohydrates, fats, minerals and vitamins. The complete vitamin content in tomatoes is believed to cure various diseases. The research objective was to financially analyze the effect of the interaction between dosage and application of organic liquid fertilizer on tomato plant production and the income of tomato farmers. The hypothesis of this study is that it is suspected that the use of organic liquid fertilizers to the production of tomato plants is financially beneficial. This research was arranged in a randomized block design (RBD) in a factorial pattern. Consists of two factors, namely: the first factor is the type of liquid organic fertilizer (P) which consists of two levels, namely liquid organic fertilizer from seaweed (P1) and liquid organic fertilizer from organic matter (P2) and the second factor is the dose of liquid organic fertilizer ( D) which consists of four levels. The use of seaweed liquid organic fertilizer increases the number of leaves, the number of flowers, and the number of fruit of the tomato plant. The weight of tomatoes also increased from 15,972 kg per hectare to 28,240 kg per hectare. So that financially there is also an increase in farmer income from Rp. 19,318,305, - to Rp. 54,652,305, - or an increase of 182.90%. It is suggested in further research to try the utilization of this organic seaweed fertilizer in other vegetable crops.